Antibacterial Properties of a Honeycomb-like Pattern with Cellulose Acetate and Silver Nanoparticles - Hurtuková, Klaudia; Fajstavrová, Klára; Rimpelová, Silvie; Vokatá, Barbora; Fajstavr, Dominik; Kasálková, Nikola Slepičková; Siegel, Jakub; Švorčík, Václav; Slepička, Petr (Materials (Basel, Switzerland), 2021)
This study involved the preparation and characterization of structures with a honeycomb-like pattern (HCP) formed using the phase separation method using a solution mixture of chloroform and methanol together with cellulose acetate. Fluorinated ethylene propylene modified by plasma treatment was used as a suitable substrate for the formation of the HCP structures. Further, we modified the HCP structures using silver sputtering (discontinuous Ag nanoparticles) or by adding Ag nanoparticles in PEG into the cellulose acetate solution. The material morphology was then determined using atomic force microscopy (AFM) and scanning electron microscopy (SEM), while the material surface chemistry was studied using energy dispersive spectroscopy (EDS) and wettability was analyzed with goniometry. The AFM and SEM results revealed that the surface morphology of pristine HCP with hexagonal pores changed after additional sample modification with Ag, both via the addition of nanoparticles and sputtering, accompanied with an increase in the roughness of the PEG-doped samples, which was caused by the high molecular weight of PEG and its gel-like structure. The highest amount (approx. 25 at %) of fluorine was detected using the EDS method on the sample with an HCP-like structure, while the lowest amount (0.08%) was measured on the PEG + Ag sample, which revealed the covering of the substrate with biopolymer (the greater fluorine extent means more of the fluorinated substrate is exposed). As expected, the thickness of the Ag layer on the HCP surface depended on the length of sputtering (either 150 s or 500 s). The sputtering times for Ag (150 s and 500 s) corresponded to layers with heights of about 8 nm (3.9 at % of Ag) and 22 nm (10.8 at % of Ag), respectively. In addition, we evaluated the antibacterial potential of the prepared substrate using two bacterial strains, one Gram-positive of S. epidermidis and one Gram-negative of E. coli. The most effective method for the construction of antibacterial surfaces was determined to be sputtering (150 s) of a silver nanolayer onto a HCP-like cellulose structure, which proved to have excellent antibacterial properties against both G+ and G- bacterial strains.
Keywords: silver nanoparticles; surface nanostructures; antibacterial properties; active materials; silver sputtering; antimicrobial activity; honeycomb-like pattern; biopolymers; surface morphology